The reality of rural education in time of pandemic. (2022)
This reflective writing arises from my personal experience and perspective regarding the situation that, in this time of pandemic, rural education in our country experiences, where great challenges and difficulties are faced in the search to give continuity to the educational process and avoid school dropout; challenges that arise due to the undeniable margin of inequality, especially in relation to the issue of connectivity, the availability of resources, the quality of support, poverty, family problems, and many other external situations that affect the learning process of students at all times, but due to for the current situation, they have become decisive factors and deserve special attention. It’s there when the following question emerges: is it possible to guarantee the right to education of quality, even when the digital gap continues to expand and economic resources are scarce in the homes of Colombian students? In order to answer this question, the measures and guidelines issued by the Ministry of National Education are covered and it will also be exposed, from a critical perspective, how each one of these is favorable or unfavorable in a context such as the one mentioned and with the former problems stated. Finally, the reflection is closed, extolling the valuable work of teachers, who, for the most part, have done their best to respond with force and truthfulness to this unthinkable moment in world history and the invitation to rethink about the education that It is intended to be offered from our educational institutions is extended.